Counter-practices of global life: A response to Claire Smith - Shepherd, Nick (2012)
We had hoped for a substantive response around the argument presented in ‘What’s up with WAC?’, instead Claire Smith has responded with a list of what she styles as ‘errors of fact and errors of representation’. Nevertheless, we thank her for the attention with which she has read our paper, and we look forward to the ‘more discursive response’ which she indicates will be forthcoming. A careful reading of Smith’s response yields fi ve points at which she correctly identifi es errors of fact in our paper. So, for the sake of the record, and in the interests of getting this over with, here goes: • It is correct that most of the books distributed through the Global Libraries Programme are new rather than second-hand; • It is correct that Colombia’s bid for WAC-6 competed against Ireland rather than Jamaica, after Jamaica’s bid had been rejected; • It is correct that the room of the WAC/ Rio Tinto meeting in Melbourne was not — literally — ‘full of lawyers’. Rather, the tone of the proceedings was legalistic, and signifi cant Rio Tinto input came from ‘community agreements’ and ‘community relations’ specialists with legal training; • The sentence ‘WAC would become an archaeological/scientifi c organization whose salaried offi ce holders were paid by Rio Tinto’, should read ‘WAC would become an archaeological/scientifi c organization whose salaried secretariat was paid by Rio Tinto’; • The countries proposed for the WAC/ Rio Tinto try-out were not Cameroon and Argentina as stated, but Gabon and Argentina.